The expression of apolipoproteina1 and its correlation with infiltration of urologic neoplasm - Hu, Huihui; Gong, Bei; Zhang, Man (Translational Cancer Research; Vol 9, No 2 (February 28, 2020): Translational Cancer Research, 2020)
Background: To explore the differential expression of apolipoproteinA1 (APOA1) in urologic neoplasm patient compared with controls, as well as investigates whether APOA1 correlated with infiltration of urologic neoplasm. Methods: A total of 59 tissue sections of surgically-resected urologic neoplasm and 6 cases of normal tissue sections were collected. Fourteen cases of urine samples from transitional cell carcinoma patients and 6 cases urine samples from controls were also applied in this experiment. We also selected 6 cases of fresh bladder transitional cell carcinoma tissues. The urologic neoplasm tissue sections were classified into infiltration and non-infiltration urologic neoplasm groups. The expressions of APOA1 between urologic neoplasm and normal control were detected by Western blot, Immunohistochemistry and qRT-PCR. The method of Immunohistochemistry was applied to examine the differences of APOA1 expression between infiltration and non-infiltration urologic neoplasm tissue section groups. Results: Compared with none expression in normal controls, APOA1 was exhibited higher level in urologic neoplasm patient’s urine and fresh bladder transitional cell carcinoma tissues (P